KEDUDUKAN HUKUM PEMBELIAN KEMBALI SAHAM (BUYBACK) OLEH EMITEN DI PASAR MODAL INDONESIA - Afrilya Aura Putri; Ruth Sarah Magdalena (UNES Law Review, 2023)
Issuers or public companies with the intention of increasing share liquidity will gain profits by selling back shares after the price has increased or as a measure to reduce paid-up capital. The act of buying back shares on the stock exchange is specifically regulated in the provisions of the law so that strict supervision is required in its implementation. The buyback of shares in the Indonesian capital market is regulated in UU No. 40 of 2007 concerning Limited Liability Companies and Bapepam-LK (OJK) Regulation Number XI.B.2 which specifically regulates Public Companies, while in market conditions that have the potential for crisis, the provisions of the Financial Services Authority Regulation No.2/POJK.04/2013 apply regarding the buyback of shares issued by Issuers or Public Companies in Significantly Fluctuating Market Conditions.